Finding and eliminating the reservoirs: Engage and treat, and test and treat strategies for lymphatic filariasis programs to overcome endgame challenges - de Souza, Dziedzom K.; Otchere, Joseph; Sumboh, Jeffrey G.; Asiedu, Odame; Opare, Joseph; Asemanyi-Mensah, Kofi; Boakye, Daniel A.; Gass, Katherine M.; Long, Elizabeth F.; Ahorlu, Collins S. (Frontiers in Tropical Diseases, 2022)
Many lymphatic filariasis (LF) endemic countries, including Ghana, have successfully implemented mass drug administration (MDA) and made significant progress towards the elimination of the disease as a public health problem. Unfortunately, the existence of individuals who seldom or never take part in MDA pose a threat to this success, as they may serve as reservoirs of infection, re-infecting their communities. In this study we implemented strategies to identify and treat these individuals, while also assessing their level of infection, to inform programme actions. The study was undertaken in the Ahanta West hotspot district in Ghana, which has received more than 17 rounds of MDA. Through the community registers used in recording participation in MDAs, we identified and offered treatment to individuals who were ineligible or inadvertently missed the last MDA in April 2021 (Engage and Treat – E&T), or testing using the filariasis test strip followed by treatment to community members who for various reasons chose not to participate in the last MDA (Test and Treat – T&T). During the study, 23,879 individuals ranging from 5 to 98 years were reached, of whom 78% were not captured in the MDA register. Among the E&T group, 75.06% willingly received and swallowed the treatment drugs. The remaining 24.94% were offered testing followed by a re-engagement to receive the drug in the T&T group. Overall, 22,830 (95.61%) of participants were treated by either strategy. Of the participants in the T&T group, 516 (8.66%; 95% CI= 7.96 – 9.41) were positive by the FTS. The highest antigen prevalence was detected among children 5 to 10 years, with 16.59% (95% CI= 12.02 – 22.06) and 22.54% (95% CI= 17.11 – 28.74) among females and males, respectively. Mapping of the data revealed that most infections are in a few select communities. Of the 516 FTS positives, 27.33% reportedly missed MDA once, 18.41% missed MDA twice and 54.26% missed all of the last three MDAs. The main reasons for missing MDA included absence (25.49%), travel (21.24%), being unaware of MDA (20.27%), refusals to take the drug (10.65%), illnesses (7.07%) and fear of adverse events (6.13%). This study demonstrates that greater sensitization and engagement strategies, with a test and treat strategy reserved for the most hesitant individuals, could significantly increase the number of individuals who receive treatment and therefore help districts reach their elimination targets by reducing the remaining reservoir or infection. NTD programmes require new tools to help them identify, engage and treat these individuals, as part of their overall monitoring and evaluation strategy.